Forced flexibility and remote working: opportunities and challenges in the new normal. (26th November 2021) - Franken, Esme; Bentley, Tim; Shafaei, Azadeh; Farr-Wharton, Ben; Onnis, Leigh-ann; Omari, Maryam
Abstract: Coronavirus disease 2019 (COVID-19) has seen a shift in remote work from being a discretionary flexible work policy to a mandatory requirement for several workplaces. This 'forced flexibility' has meant that organisations and their employees have had to adapt swiftly to new requirements and arrangements for how work is done. Working remotely, often at home in 'virtual workspaces', has become commonplace for many employees across Australia and globally. Drawing on findings from two qualitative phases of research in an Australian resources company, we use conservation of resources theory to explore the factors influencing processes related to wellbeing and productivity for employees working remotely in the COVID-19 environment. We identify challenges associated with working remotely, as well as important resources for wellbeing and productivity. Practical implications are also discussed.